Lysosomal acid lipase deficiency – early diagnosis is the key - Strebinger, Georg (Hepat Med, 2019)
Lysosomal acid lipase deficiency (LAL-D) is an ultra-rare lysosomal storage disease that may present from infancy to late adulthood depending on residual enzyme activity. While the severe form manifests as a rapidly progressive disease with near universal mortality within the first 6 months of life, milder forms frequently go undiagnosed for prolonged periods and typically present with progressive fatty liver disease, enlarged spleen, atherogenic dyslipidemia and premature atherosclerosis. The adult variant of LAL-D is typically diagnosed late or even overlooked due to the unspecific nature of the presenting symptoms, which are similar to common changes observed in the context of the metabolic syndrome. This review is aimed at delineating clinically useful scenarios in which pediatric or adult medicine clinicians should be aware of LAL-D as a differential diagnosis for selected patients. This is particularly relevant as a potentially life-saving enzyme replacement therapy has become available and the diagnosis can easily be ruled out or confirmed using a dried blood spot test.